2014
DOI: 10.1093/eurheartj/eht546
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus-eluting bioresorbable vascular scaffolds for treatment of patients presenting with ST-segment elevation myocardial infarction: BVS STEMI first study

Abstract: In the present series, the BVS implantation in patients presenting with acute MI appeared feasible, with high rate of final TIMI-flow III and good scaffold apposition. Larger studies are currently needed to confirm these preliminary data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 36 publications
4
59
0
3
Order By: Relevance
“…Results from available observational studies and randomized clinical trials are reassuring and very promising (16)(17)(18)(19)(20)(21)(22)(23). Rates of early BVS thrombosis in adverse anatomic scenarios, including the presence of a highly thrombogenic milieu, however, appear to be not negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Results from available observational studies and randomized clinical trials are reassuring and very promising (16)(17)(18)(19)(20)(21)(22)(23). Rates of early BVS thrombosis in adverse anatomic scenarios, including the presence of a highly thrombogenic milieu, however, appear to be not negligible.…”
Section: Discussionmentioning
confidence: 99%
“…The everolimus-eluting bioresorbable vascular scaffolds for treatment of patients presenting with ST-segment elevation myocardial infarction (BVS STEMI) study was the first that evaluated BRS use in STEMI (103 The investigators reported good procedural and clinical outcome in these patients, but with stent thrombosis rate of 2.4%, higher than that seen in clinical trials (106). An excellent review of BRS use in STEMI has been published elsewhere (107) and the authors stated that the unique properties of the BRS make STEMI the ideal scenario for BRS implantation.…”
Section: Brs Use In Stemi Patientsmentioning
confidence: 99%
“…Success rates were defined as in previous studies with BVS implantation [15,16]. Device success was described as the presence of residual diameter stenosis < 30% of the segment of the culprit lesion, covered by the BVS, assessed by angiographic visual estimation.…”
Section: Coronary Angiography and Oct Analysesmentioning
confidence: 99%
“…The latter phenomenon is associated with the dissolution of the thrombus sequestrated between the BVS struts and the vessel wall [13,14]. There are only few reports with a comprehensive optical coherence tomography (OCT) evaluation of the BVS implantation in this group of patients [15,16]. To add more data to the current limited body of evidence, we performed a pilot study with a qualitative and quantitative OCT examination to assess vessels' response to the implanted BVS and the performance of the new device in culprit lesions in patients presenting with ST segment elevation myocardial infarction (STEMI).…”
Section: Introductionmentioning
confidence: 99%